The gastrointestinal (GI) tract - Drake, Richard L. (Henry Stewart Talks, 2021)
The abdominal viscera, Peritoneum, The mesentery and omentum, Stomach vasculature, The duodenum and its vasculature, The jejunum and ileum, The large intestine, Abdominal vasculature, The celiac trunk and the superior mesenteric artery, Inferior mesenteric artery, Venous drainage